Nursing education: Flipping the classroom. Issue 2 (18th February 2016) - Hessler, Karen L.
Abstract : Abstract: This article will introduce the innovative educational concept of the "flipped classroom." How to implement the flipped learning model will be addressed within the framework of The Intentional Instruction Environment Model. Abstract : This article introduces the innovative educational concept of the "flipped classroom." How to implement the flipped learning model is addressed within the framework of The Intentional Instruction Environment Model.